SEPTICTANK PERESAPAN SISTEM KANAL (PERSIKAN) SEBAGAI TEKNOLOGI ALTERNATIF PENGENDALIAN PENCEMARAN KOLIFORM TINJA PADA PEMUKIMAN PADAT - Yanto Yanto; Nastain Nastain (Jenderal Soedirman University, 2007)
The main problem of domestic wastewater treatment in term of bacterial removal using conventional septictank in many developed towns is lack of land to purify domestic sewage into 10 m minimum safety distance according to WHO regulation. It is necessary to develop new treatment system to ensure bacterial will be removed 100 percent less than 10 m distance. Channel System Filter Septictank (CSF Septictank) is designed to solve the problem above. CSF Septictank is a common septictank equipped with filter tank separated by several partition walls to shape channels. CSF will consist of three parts: initial storage tank, filter tank and final storage tank. The Filter tank is fully filled with fine sand as filter medium. Wastewater will flows from the initial storage tank then pass the filter tank and entering the final storage tank as product of CSF Septictank treatment. Dimensions of the filter tank are analyzed using Huisman formula. Performance of CSF Septictank is measured by comparing water quality between water in the initial storage tank and the final storage tank. Water quality test result shows significance effect in bacterial removal. The other parameters also show increasing of water quality. By using CSF Septictank, bacterial contents could be removed 99,15%, BOD5 contents decreases 27,24%, COD contents decreases 29,01% meanwhile DO contents increases 27,78%